1998
DOI: 10.1016/s0266-7681(98)80014-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome of Anterior Transposition of the Vascularized Ulnar Nerve for Cubital Tunnel Syndrome

Abstract: Anterior transposition of the ulnar nerve is a widely used treatment for cubital tunnel syndrome, but neurolysis performed at the time of surgery may impair the blood supply to the ulnar nerve. This study compared the results of intramuscular anterior transposition of the ulnar nerve with or without preserving the extrinsic vessels of the ulnar nerve in 35 patients. The postoperative nerve conduction velocity and the clinical results were better in the group in which the extrinsic vessels were presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 20 publications
0
12
0
6
Order By: Relevance
“…However, in some studies, this technique was reported to have less favorable results and increased risk of complications when compared with both in situ decompression and medial epicondylectomy. [18][19][20][21]25] These drawbacks of transposition techniques are related to compromised vascularity and intraneural microcirculation of the ulnar nerve. [25,26] Medial epicondylectomy has been shown to decrease ulnar nerve strain at the elbow which is accepted as a cause of CuTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some studies, this technique was reported to have less favorable results and increased risk of complications when compared with both in situ decompression and medial epicondylectomy. [18][19][20][21]25] These drawbacks of transposition techniques are related to compromised vascularity and intraneural microcirculation of the ulnar nerve. [25,26] Medial epicondylectomy has been shown to decrease ulnar nerve strain at the elbow which is accepted as a cause of CuTS.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21]25] These drawbacks of transposition techniques are related to compromised vascularity and intraneural microcirculation of the ulnar nerve. [25,26] Medial epicondylectomy has been shown to decrease ulnar nerve strain at the elbow which is accepted as a cause of CuTS. [3,11,27] To address the tethering effect of this anatomical structure on ulnar nerve, different types of medial epicondylectomy techniques have been described with satisfactory clinical results.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the controversy of the operative procedure for carpal tunnel syndrome is the method by which to release the ligament but most surgeons would agree that successful management of patients with carpal tunnel syndrome depends on complete release of the flexor retinaculum [1,3,6,17,22]. In contrast for cubital tunnel syndrome, there are numerous operative procedures that have been described for the treatment of cubital tunnel syndrome ranging from simple decompression, medial epicondylectomy to transposition of the ulnar nerve [2,4,7,9,12,13,14,15,16,19,21,23,24,25,26,27,29,30,31]. These procedures vary not only in surgical technique but also in the correction of the etiologic factors.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous operative procedures described for the treatment of cubital tunnel syndrome ranging from simple decompression, medial epicondylectomy to transposition of the ulnar nerve [2,4,7,9,12,13,14,15,16,19,21,23,24,25,26,27,29,30,31]. With each operative procedure, there have been reports of excellent patient outcome as well as postoperative complications [10,11,18,28].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 It may be the most common surgical procedure for cubital tunnel syndrome. 8,9 Techniques to maintain the nerve anterior to the medial epicondyle include subcutaneous pocket, 3,7 subcutaneous fascia tunnel, 10 and fascial 6 and fasciodermal 11 sling. Pribyl and Robinson 6 described a method that incorporates the medial intermuscular septum into a fascial sling to prevent posterior subluxation of the transposed nerve.…”
mentioning
confidence: 99%